2018
DOI: 10.1101/478131
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dissociable Neural Correlates of Uncertainty Underlie Different Exploration Strategies

Abstract: SummaryMost real-world decisions involve a delicate balance between exploring unfamiliar alternatives and committing to the best known option. Uncertainty lies at the core of this “explore-exploit” dilemma, for if all options were perfectly known, there would be no need to explore. Yet despite the prominent role of uncertainty-guided exploration in decision making, evidence for its neural implementation is still sparse. We investigated this question with model-based fMRI (n = 3… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(40 citation statements)
references
References 67 publications
(104 reference statements)
5
35
0
Order By: Relevance
“…Methods, Equations 1,2). We included three additional factors: First, because recent evidence suggests that exploration is aimed at reducing the outcome-variability associated with different options (Badre et al, 2012;Frank et al, 2009;Tomov et al, 2020), we included an outcome-variability factor which was updated by a prediction-error scaled by a learning-rate (Equations 6-7). Second, an additional exploratory strategy that allows detecting changes in the environment is randomly switching machines between trials, and we therefore included a random-switching binary factor (Equation 9).…”
Section: Behavioral Factors Contributing To Explorationmentioning
confidence: 99%
See 3 more Smart Citations
“…Methods, Equations 1,2). We included three additional factors: First, because recent evidence suggests that exploration is aimed at reducing the outcome-variability associated with different options (Badre et al, 2012;Frank et al, 2009;Tomov et al, 2020), we included an outcome-variability factor which was updated by a prediction-error scaled by a learning-rate (Equations 6-7). Second, an additional exploratory strategy that allows detecting changes in the environment is randomly switching machines between trials, and we therefore included a random-switching binary factor (Equation 9).…”
Section: Behavioral Factors Contributing To Explorationmentioning
confidence: 99%
“…Exploration was shown to increase with environmental volatility (Knox et al, 2012), and evidence suggest that exploratory decisions are directed towards options with large outcome variabilities (Badre et al, 2012;Cavanagh et al, 2012;Kayser et al, 2015;Tomov et al, 2020). Imaging studies in humans have shown that exploratory decisions engage the anterior insulae (aINS) as well as prefrontal regions involved in executive control processes, such as the frontopolar cortex (FPC) and the dorsal anterior cingulate cortex (dACC) (Badre et al, 2012;Blanchard and Gershman, 2018;Cavanagh et al, 2012;Daw et al, 2006;Kayser et al, 2015;Laureiro-Martinez et al, 2015;Tomov et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, in environments with changing volatility, different computations underlying decision-making and learning might play an essential role 58,59 . Another caveat is that, while we relate choice stochasticity and preference for previously unchosen options to random and uncertainty-driven exploration strategies respectively, more sophisticated experimental tasks are required for in-depth examinations of the nature of the exploration strategies 8,10,12,60 . Furthermore, while we have shown the correlation between one dimension of psychiatric symptoms and particular computational processes in decision-making, we have left open the question as to how these two are causally related.…”
Section: Discussionmentioning
confidence: 99%